Warnings against Myself : Meditations on a Life in Climbing - Stevenson, David (David Dougal) (Book collections on Project MUSE., 2016)
"Personal essays detailing noteworthy climbing sites throughout the western United States, infused with a few terrifying excursions to the Alps and a trip to the Bugaboos of western Canada, Warnings Against Myself opens up the beautiful, obsessive world of mountain climbing to climbers and non-climbers alike. From his youthful second ascent of the north ridge of Mount Kennedy in the Yukon's Saint Elias Range, an in-and-out on skis for which he had not entirely learned how to ski, to a recent excursion across the Harding Icefield in the Kenai Mountains of the Kenai Peninsula in Alaska conceived under the influence of rain and whiskey, David Stevenson chronicles several decades of a life unified by a preoccupation with climbing. Stevenson describes climbing first-hand, but also reflects on climbing in a beautiful way that draws in both literary references and engaging characterizations of well-known climbers. His changing viewpoint on his dangerous obsession as he ages, marries, and has children (and then takes his son climbing) give the book a strong shape, and the work as a whole adds a new and thoughtful perspective to the literature of climbing."--